Eksplicitacija v prevodih političnih govorov - Šumrada, Simona (Jezik in slovstvo, 2009)
In 2008, Slovenia and France presided over the European Union. Both countries published translations of speeches and other public communication on the Internet. In view of the relative comparability of the situation in which the translations came about, it would be interesting to undertake a complete analysis of the documents translated within the framework of the two state institutions. The present article is limited to an analysis of phenomena linked with explicitation, as they appear in translations into French and English with regard to the Slovene original. It is based on a parallel and comparative section of a corpus of political speech texts. The results of quantitative and, to a lesser extent, qualitative analysis are presented, based primarily on the explicitation of demonstrative pronouns in noun usage. In translations of Slovene political speeches these are often replaced by noun anaphora, which is a stronger cohesive link.
Keywords: eksplicitacija; kohezija; konceptualna anafora; politični govori; prevajanje; prevodi v slovenščino; prevodoslovje; translation; translation studies